Ethanol and colorectal carcinogenesis - Seitz, Helmut K.; Simanowski, Ulrich (Colorectal cancer: from pathogenesis to prevention?, 1989)
Ethanol has to be considered as one of the most important toxins consumed regularly and in high quantities by humans. Throughout history, alcoholic beverages have been widely used for their pleasant taste and their mood-altering effects. However, during the last few decades alcohol consumption has steadily increased worldwide, and alcoholism has become one of the major health problems. Haevy alcohol ingestion exerts a deleterious effect on almost every organ and tissue of the human body. The most important ethanol-related diseases are hepatic cirrhosis, pancreatitis, cardiomyopathy, hematological and neurological disorders, infections such as tuberculosis, and tumor development.